2013
DOI: 10.3319/tao.2013.05.23.01(oc)
|View full text |Cite
|
Sign up to set email alerts
|

Field Observations of Changes in SST, Chlorophyll and POC Flux in the Southern East China Sea Before and After the Passage of Typhoon Jangmi

Abstract: Severe tropical storms play an important role in triggering phytoplankton blooms, yet direct field observation of evidence of the effects of a typhoon is very rare. Sea surface temperature (SST), nitrate concentration, chlorophyll a (chl a) concentration, and particulate organic carbon (POC) flux were measured before and shortly after Typhoon Jangmi which affected the southern East China Sea (SECS) on September 28 ~ 29, 2008. In situ SST (27.5 ~ 28.0°C) on September 19 ~ 21, decreased to ~24.0°C (October 3 ~ 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 50 publications
(88 reference statements)
1
17
0
Order By: Relevance
“…Moreover, the ocean‐atmosphere interactions and fisheries data collected before and after the passage of several typhoons across the southern region of the ECS suggested that typhoons can enhance upwelling that results not only in increases of Chl a but also in changes of local fish communities and, consequently, fishing activities [ Chang et al ., ]. Typhoon‐induced upwelling can indeed stimulate efficient particulate organic carbon export out of the euphotic zone [ Shih et al ., ]. In the waters near the typhoon's path, especially in the typhoon‐induced upwelling area, nutrient‐rich bottom water stirred by the typhoon can promote an outbreak of aquatic organisms and significantly increase the probability of red tide occurrence [ Li et al ., ].…”
Section: Progress Of Upwelling Studies In the China Seasmentioning
confidence: 99%
“…Moreover, the ocean‐atmosphere interactions and fisheries data collected before and after the passage of several typhoons across the southern region of the ECS suggested that typhoons can enhance upwelling that results not only in increases of Chl a but also in changes of local fish communities and, consequently, fishing activities [ Chang et al ., ]. Typhoon‐induced upwelling can indeed stimulate efficient particulate organic carbon export out of the euphotic zone [ Shih et al ., ]. In the waters near the typhoon's path, especially in the typhoon‐induced upwelling area, nutrient‐rich bottom water stirred by the typhoon can promote an outbreak of aquatic organisms and significantly increase the probability of red tide occurrence [ Li et al ., ].…”
Section: Progress Of Upwelling Studies In the China Seasmentioning
confidence: 99%
“…Many coastal areas in China have a large population and fast-growing economy, which together result in declining water quality, enhanced eutrophication and algal blooms, loss of biodiversity and widespread degradation of aquatic ecosystem services. Direct measurement of nutrient dynamics during storms in China coastal river is very limited (Yang et al, 2009;Wu et al, 2012), although several scientists have conducted similar biogeochemical research after strong storm events in Chinese coastal waters (Gong et al, 2011;Hung et al, 2013;Shih et al, 2013;Chen et al, 2013a). Insufficient knowledge of how storm alter riverine nutrient supply impedes our ability to understand the regional changes that affect coastal ecosystems, and limits our ability to guide management and decision making.…”
Section: Introductionmentioning
confidence: 97%
“…Studies using the integrated Global NEWS model have predicted increased riverine export of dissolved nutrients (mainly nitrogen (N) and phosphorus (P)) from watersheds to the coast by the year 2030, particularly in Asian basins such as China if economic development continues (Qu and Kroeze, 2010;Seitzinger et al, 2010). The cumulative effects of global environmental and climate change will likely cause an increased inflow of freshwater and nutrients to coastal waters in many areas of the globe, intensifying the eutrophication of estuarine and coastal waters (Rabalais et al, 2009;Hung et al, 2013;Shih et al, 2013;Chen et al, 2013a). Increasing nutrient losses from terrestrial to aquatic ecosystems are frequently associated with intensification of agriculture, application of animal wastes and chemical fertilizer to farmland, as well as uplands and channel erosion.…”
Section: Introductionmentioning
confidence: 99%
“…Many publications have shown that episodic extreme weather events (EWEs) significantly enhance biogeochemical responses in estuarine environments [ Shiah et al ., ], coastal, and/or marginal seas [ Shiah et al ., ; Yuan and Zhang , ; Hung et al ., ; Chen et al ., ; Liu et al ., ; Shih et al ., ]. Hung et al .…”
Section: Introductionmentioning
confidence: 99%